Phononic nodal point in two dimensions: A mini-review - Yang, Ying (Frontiers in Physics, 2022)
In recent decades, nodal point states in electronic systems have attracted significant interest in current research. Recently, the conceptual framework of nodal point states has been extended to bosonic systems, especially the phononic one. It is well known that the nodal point states may exist much more universally in materials other than topological electronic systems. Fortunately, a series of nodal point phonons are reported in three-dimensional realistic materials, and some are certified in experiments. However, to our knowledge, the study of phononic 2D nodal points is still relatively primitive. Hence, a highlight of research in the emerging area covering approximately the last two-three years is necessary. This mini-review will summary the recent advances in the phononic nodal point in two dimensions. Some typical examples, including graphene, CrI3 monolayer, YGaI monolayer, TiB4 monolayer, Ti2P monolayer, and Cu2Si monolayer, are concluded in this mini-review. The topological properties and possible applications of these material candidates are also summarized.